Perturbations of degenerate coisotropic invariant tori of Hamiltonian systems - Parasyuk, I. O. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider a Hamiltonian system with a one-parameter family of degenerate coisotropic invariant tori. We prove a theorem on the preservation of the majority of tori under small perturbations of the Hamiltonian.